Changes in Expression of DNA-Methyltransferase and Cannabinoid Receptor mRNAs in Blood Lymphocytes After Acute Cannabis Smoking - Smith, Robert C.; Sershen, Henry; Janowsky, David S.; Lajtha, Abel; Grieco, Matthew; Gangoiti, Jon A.; Gertsman, Ilya; Johnson, Wynnona S.; Marcotte, Thomas D.; Davis, John M. (Frontiers in Psychiatry, 2022)
Background: Cannabis is a component risk factor for schizophrenia. The biological effects of cannabis include effects on epigenetic systems, immunological parameters, in addition to changes in cannabinoid receptors 1 and 2, that may be associated with this risk. We analyzed the effects of two concentrations of tetrahydrocannabinol (THC) vs. placebo in lymphocytes. Methods: 24 participants who regularly use cannabis participated in an experiment in which they smoked cannabis cigarettes (5.9% or 13.4% THC) or placebo (0.02%). Lymphocytes were analyzed for mRNA content for cannabinoid receptors 1 (CB1) and 2 (CB2), methylation and demethylating enzymes (DNMT, TET), glucocorticoid receptor (NRC3) and immunological markers (IL1B, TNFα) by qPCR using TaqMan probes. The results were correlated with THC whole blood levels during the course of the day, as well as THCCOOH baseline levels. Results: Both the 5.9% and 13.4% THC groups showed increased THC blood levels and then decreased toward baseline within the first hour. At the 4-hour time point after drug administration the 13.4% THC group had higher CB2 (P=.021) and DNMT3A (P=.027) mRNA levels than the placebo group. DNMT1 mRNA levels showed a trend in the same direction (P=.056). The higher 13.4% THC group had significantly increased CB2 mRNA levels than the 5.9% concentration group at several post drug administration time points. TET3 mRNA levels were higher in the 13.4% THC group at 55 minutes post-cannabis ingestion. When the high and lower concentration THC groups were combined, none of the differences in mRNA levels from placebo remained statistically significant. Changes in THC blood levels were not related to changes in mRNA levels. Conclusions: Over the time course of this study, CB2 mRNA increased in blood lymphocytes in the high concentration THC group but were not accompanied by changes in immunological markers. The changes in DNMT and TET mRNAs suggest potential epigenetic effects of THC in human lymphocytes. Increases in DNMT methylating enzymes have been linked to some of the pathophysiological processes in schizophrenia and, therefore, should be further explored in a larger sample population, as one of the potential mechanisms linking cannabis use as a trigger for schizophrenia in vulnerable individuals.